PERANCANGAN MEDIA PROMOSI DALAM KEPATUHAN MENGKONSUMSI GERTELLA TERHADAP PENURUNAN TEKANAN DARAH PADA PRA LANSIA DI KOTA BENGKULU - Linda, Linda; Triana, Winda; Anggraini, Desi Veti (JURNAL MEDIA KESEHATAN, 2023)
Non-communicable diseases (NCDs) are a major factor that can cause death in the world. The use of natural ingredients such as rosella plant (Hibicus Sabdarifa Fam), is one way that can be done to lower blood pressure. This rosella plant can have an effect on reducing serum creatinine, cholesterol, and glucose levels because it contains chemical compounds. The gertella application can make it easier to helping compliance compliance with consuming gertella. The purpose of this study was to determine the effect of promotional media in compliance with consuming gertella as an effort to reduce blood pressure. The research uses quasi-experimental two group pretest and posttest design. Respondents consumed rosella tea 1-2 perfect petals (2 grams) per day for seven days. The samples consisted of 30 gertella applications groups and 30 whatsapp group. The results of the study in the gertella application group there was a difference in mean systolic blood pressure before and after the intervention with = 0.000 <0.05. There was a difference in mean diastolic blood pressure before and after the intervention with = 0.003 <0.05. In the whatsapp group there was a difference in mean systolic blood pressure before and after the intervention with = 0.019 < 0.05. There was a difference in the mean diastolic blood pressure before and after the intervention with = 0.009. Conclusion there is an effect of gertella application on compliance in lowering blood pressure in the elderly.